2017
DOI: 10.1007/978-3-319-57789-0
|View full text |Cite|
|
Sign up to set email alerts
|

Intervening After Violence

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Family systems theory offers a more ecologically informed, less linear, understanding of violence within families. This includes an analysis of the function of violence in a particular family, as well as how the complex patterns of communication, narratives and feedback loops perpetuates and maintains violent behaviour between different parts of the system (Sammut Scerri et al, 2017). A recent systematic review found evidence to support the use of family therapy in the reduction of IPV (Stith et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Family systems theory offers a more ecologically informed, less linear, understanding of violence within families. This includes an analysis of the function of violence in a particular family, as well as how the complex patterns of communication, narratives and feedback loops perpetuates and maintains violent behaviour between different parts of the system (Sammut Scerri et al, 2017). A recent systematic review found evidence to support the use of family therapy in the reduction of IPV (Stith et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However the dilemma around families that are managing IPV is, how much can you work with a system that is actively dangerous and where the practitioner has ethical and statutory responsibilities to keep people safe alongside a therapeutic task? Some of the nuances of holding this position are addressed in systemic work that directly addresses IPV (Sammut Scerri et al, 2017) and a fuller discussion of the need for a both/and flexible approach to practice will be elucidated in the implications section. In cases of extreme unpredictability and endangerment however, anything other than functional parenting may be impossible, and professionals are duty bound to act in these circumstances.…”
Section: Trauma Responses As Adaptive But Distracting Coping Strategiesmentioning
confidence: 99%
See 3 more Smart Citations